2021
DOI: 10.1172/jci.insight.146197
|View full text |Cite
|
Sign up to set email alerts
|

Splicing factor SRSF6 mediates pleural fibrosis

Abstract: Pleural fibrosis is defined as an excessive deposition of extracellular matrix that results in destruction of the normal pleural tissue architecture and compromised function. Tuberculous pleurisy, asbestos injury and rheumatoid pleurisy are main causes of pleural fibrosis. Pleural mesothelial cells (PMCs) play a key role in pleural fibrosis. However, detailed mechanisms are poorly understood. Serine/arginine-rich protein SRSF6 belongs to a family of highly conserved RNA-binding splicing-factor proteins. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…. We also implement R-GCN [36] with TorchSparse++ and benchmark it on five representative heterogeneous graph datasets against state-of-the-art graph deep learning systems DGL [44], PyG [16] and the Graphiler [46]…”
Section: Resultsmentioning
confidence: 99%
“…. We also implement R-GCN [36] with TorchSparse++ and benchmark it on five representative heterogeneous graph datasets against state-of-the-art graph deep learning systems DGL [44], PyG [16] and the Graphiler [46]…”
Section: Resultsmentioning
confidence: 99%
“…SRSF6 may also be involved in the cell proliferation of some normal cells. Liang et al showed that SRSF6 knockdown significantly inhibited cell proliferation of pleural mesothelial cells stimulated by inflammation ( Liang et al, 2021 ). In neuron cells, SRSF6 helps maintain microtubule stability by promoting the inclusion of Tau exon 10, which is important for the assembly and stability of microtubule in neuron cells ( Yin et al, 2012 ).…”
Section: The Normal Cellular Functions Of Serine/arginine-rich Splicing Factormentioning
confidence: 99%
“…SRSF6 is a multi-function protein that is involved in several biological processes besides RNA splicing, including translation ( Swanson et al, 2010 ) and transcription ( Juge et al, 2010 ). Besides cancer, SRSF6 has been associated with numerous human diseases, such as pleural fibrosis ( Liang et al, 2021 ), Huntington’s disease ( Cabrera and Lucas, 2017 ), Alzheimer’s disease ( Mai et al, 2019 ), diabetes ( Juan-Mateu et al, 2018 ), and systemic sclerosis ( Manetti et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SRSF6 is a direct target of miR-506-3p, and its overexpression caused by the repression of miR-506-3p was observed in pleural fibrosis, a thickening of the membranes that cover the lungs [ 37 ]. Unfortunately, the downstream effects have yet to be directly identified.…”
Section: Rna Splicing Factors Regulated By Mirnasmentioning
confidence: 99%